Hydrogels for Cardiac Tissue Repair and Regeneration - Madalina Elena Grigore (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
The main cause of death in the world continues to be cardiovascular disease, which affects annually over 900,000 people and in the entire word approximately 50% of the people suffering myocardial infarction (MI) die within 5 years. MI causes a number of cardiac pathologies like hypertension, blocked coronary arteries and valvular heart diseases resulting ischemic cardiac injury. In the last years, cardiac tissue engineering has made considerable progress, because this progress have been made towards developing injectable hydrogels for the purpose of cardiac repair and/or regeneration. This study aims to provide an updated survey of the major progress in the fl ied of injectable cardiac tissue engineering, including biomaterials (natural, synthetic or hybrid hydrogels), their advantages or disadvantages and the main seeding cell sources. Also, this review focuses on the progress made in the field of hydrogels for cardiac tissue repair and/or regeneration for MI over the last years.